2001
DOI: 10.1046/j.1440-1819.2001.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on psychosomatic complaints by senior high school students in Tokyo and their related factors

Abstract: The purpose of this study was to clarify the relationships between psychosomatic complaints of senior high school students in Tokyo and the cognition they receive from their fathers, mothers, friends, teachers, and schoolwork and between their complaints and lifestyle habits. The subjects were 168 first-grade students (58 males and 110 females) at a Tokyo Metropolitan senior high school. In June 1996, a collective survey was carried out, using questionnaires. Moreover, I conducted a longitudinal study to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…The main symptoms in these children include headache, abdominal pain, poor early rising, nausea, fatigue, etc., and children having two or more symptoms were reported to range about 20-30% [2]. Pupils who come to school infirmaries with physical symptoms related to emotional stress has increased to more than 15% per a week [3,4]. On October 19, 1999, the research team of the Ministry of Health, Labor and Welfare performed the national survey and indicated that 8.47% children aged 10-15 years old were diagnosed with psychosomatic diseases in patients.…”
Section: Major Psychosomatic Problems In Japanese Children and Adolesmentioning
confidence: 99%
“…The main symptoms in these children include headache, abdominal pain, poor early rising, nausea, fatigue, etc., and children having two or more symptoms were reported to range about 20-30% [2]. Pupils who come to school infirmaries with physical symptoms related to emotional stress has increased to more than 15% per a week [3,4]. On October 19, 1999, the research team of the Ministry of Health, Labor and Welfare performed the national survey and indicated that 8.47% children aged 10-15 years old were diagnosed with psychosomatic diseases in patients.…”
Section: Major Psychosomatic Problems In Japanese Children and Adolesmentioning
confidence: 99%
“…Children's mental health problems seem to be attributable to stress. It has been suggested to arise from academic competition and interpersonal relations with classmates or teachers, and surveys in the past clearly show that teachers' attitudes affect children's stress [4].…”
Section: Introductionmentioning
confidence: 99%
“…From the 1990s to the new millennium, Japan has witnessed a considerable rise in the number of children presenting with psychosomatic disorders [3]. As a result of this, the number of students with physical symptoms caused by stress who come to school infirmaries has increased [4].…”
Section: Introductionmentioning
confidence: 99%
“…In senior high school students in Tokyo, the females had more psychosomatic complaints than the males [3]. In the USA, in clinical and epidemiological studies, a consistently higher frequency of depression is noted in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…Among children who consulted medical institutions in 1999, the number of children with psychosomatic disorders such as irritable bowel syndrome, headache, hyperventilation syndrome, bronchial asthma, eating disorder, and orthostatic dysregulation etc., increased with age and peaked at the age of 14 in males (18.3%) and at 15 in females (26.8%) [2] due to stress arising from academic competition and interpersonal relations with classmates or teachers in school [3] or due to poor parental interaction [4]. …”
Section: Introductionmentioning
confidence: 99%